Nano Biomass Material functionalized by β-CD@Ce(NO)3 as a high performance adsorbent to removal of fluorine from wastewater. (January 2023) - Ren, Yuanchuan; Ning, Ping; Qu, Guangfei; Ren, Nanqi; Wu, Fenghui; Yang, Yuyi; Chen, Xiuping; Wang, Zuoliang; Hu, Yan
Abstract: Fluorine pollution has become one of the key issues of water pollution, and the adsorption materials for efficient removal of fluorine ions have attracted much attention. It is rarely reported that the self-synthesized biomass materials were functionalized by the β-CD@Ce(NO)3 . This paper mainly proposed a new synthetic method of the self-synthesized biomass materials were modified by the β-CD@Ce(NO)3 and removal of fluorine ions. The effects of this materials on the adsorption efficiency of fluorine ions under different conditions were explored, and the kinetic and thermodynamic simulations were carried out. The results show that the self-synthesized biomass materials were modified by the β-CD@Ce(NO)3 has significant pore structure, large specific surface area and multi-functional group. Adsorption experiment showed that the reaction reached adsorption equilibrium at 30 min. The removal rate of fluorine ions reached 93.13%, and the fluorine ions adsorption capacity was 37.25 mg/g under neutral conditions. The material can be recycled for more than 5 times, and the adsorption efficiency remains above 94%. The adsorption kinetics accorded with the pseudo second-order model and the adsorption isotherm equation is in line with the Langmuir isotherm adsorption model. PO4 3− and CO3 2− have the most impact on fluorine ions adsorption. This method reduces the synthesis cost of high-performance adsorption materials and improves the adsorption performance, which is conducive to the popularization and application in the future. Graphical abstract: Image 1 Highlights: A simple and economical method was used for defluorination of wastewater. Nano Biomass Material functionalized by β-CD@Ce(NO)3 were efficient for the removal of low fluoride content. Fluoride removal occurred simultaneously by ion exchange, ligand exchange, complexation and electrostatic interaction. This method breaks the limitation of organic waste in application.